Fourth Progress Report on Inclusion of Enhanced Contractual Provisions in International Sovereign Bond Contract. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper reports on progress in inclusion of enhanced collective action clauses and modified pari passu clauses as of end-October 2018. The report finds that enhanced CACs have now become the market standard, with only a few issuers standing out from the market trend. Around 88 percent of international sovereign bonds (in aggregate principal amount) issued since October 2014 in the main jurisdictions of New York and England include such clauses. The modified pari passu clause continues to be incorporated as a package with the enhanced CACs, with few exceptions. In line with findings in previous reports, the inclusion of enhanced CACs does not seem to have an observable pricing effect, according to either primary or secondary market data. The outstanding stock of international sovereign bonds without enhanced CACs remains high, with about 39 percent of the outstanding stock including enhanced CACs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet